Penggunaan Aplikasi QRIS Pembayaran Non Tunai untuk Meningkatkan Transaksi Penjualan Outlet di Wisata Belanja Jeans Cihampelas Bandung - Panji Pamungkas; Nurul Syamsiah; Adiarti Budikartini (STIEPAR YAPARI Bandung, 2023)
This study aims to determine and explain the use of the QRIS application to increase outlet sales in jeans shopping tours in Cihampelas Bandung. This research uses quantitative methods with descriptive and verification analysis. The sample was a jeans outlet that used the QRIS application with as many as 68 respondents. The analysis methods used are instrument tests (validity tests, reliability tests, normality tests and linearity tests), multiple regression analysis, coefficient of determination, t-test and F test using IBM SPSS 24 for Windows. The results showed a coefficient of determination (R-square) value of 0.938 or 93.8% that all independent variables influenced the dependent variable by 93.8%. While the remaining 6.2% was influenced by other variables that were not studied in this study. QRIS purchase variables, QRIS promos, QRIS usage, QRIS usage satisfaction, partial and simultaneous influence on Cihampelas jeans outlet transactions. The conclusion of this research is the purchase of QRIS, its usefulness of QRIS, and satisfaction with the use of QRIS has a positive and significant effect on outlet sales transactions in Cihampelas Bandung jeans shopping tours.